Peningkatan Minat Lulusan Paket C PKBM Bumi Literasi Dalam Melanjutkan Studi ke Perguruan Tinggi - Dewi Shinta Wulandari Lubis; Soraya Grabiella Dinamika (Forum Kerjasama Pendidikan Tinggi, 2021)
The high school level dropout rate in North Sumatra Province in the 2019/2020 school year tends to increase. To overcome this, the previous government has created a non-formal education program known as Equality Education. In Deli Serdang Regency itself, a number of institutions that organize Equality Education have been established, one of which is the Earth Literacy Community Learning Activity Center (PKBM) which is located at Sigara-gara Village, Patumbak District. In 2021 the Earth Literacy PKBM will complete its first graduates from package A, package B, and package C. All graduates of package A and package B plan to continue their education. However, the majority of package C graduates do not want to continue their education to higher education due to various factors, including not knowing about the benefits and functions of college at all, being satisfied with only getting a high school diploma, difficulty in paying for college, already working and feeling enough. with the income that can be, choose to marry and become a housewife, etc. For this reason, the community service team from the Sukma College of Management took the initiative to inform about the benefits of college and various college scholarships, and bring students directly to share their experiences during college. From this community service activity, it was found that as many as 4 package C graduates registered directly for the KIP/K scholarship path and foundation scholarships. This shows their interest and enthusiasm for studying after getting information from the service team.